Strengthening Tolerance Character as A Form of Civic Disposition Through Community Engagement In Multicultural Societies - Elvi Nurhidayati; Suharno Suharno (International Journal Labs, 2025)
The character of tolerance is important to be developed in a multicultural country like Indonesia. Communities in society need to be developed massively to participate in providing understanding related to diversity, tolerance, and peace. This community can play a role in strengthening the character of tolerance as a form of citizenship for Indonesian citizens. This study aims to describe the role of the community in strengthening the character of tolerance based on a multicultural society, and analyze the implications of activities to strengthen the character of tolerance by the community in developing civic character. This research uses a case study method with a qualitative approach and with research techniques in the form of interviews, observations, and documentation. The data analysis in this study uses the Miles, Huberman, and Saldana model, namely data collection, data reduction, data presentation, and conclusion drawn. The results of this study show that 1) the role of the SRILI community in strengthening the character of tolerance based on a multicultural society is by holding activities such as conflict resolution training, interfaith dialogue, and overcoming prejudice. 2) Strengthening the character of tolerance can have implications for civic dispositions such as respect for diversity, being inclusive and open, respecting minority rights, commitment to Pancasila, and training critical and reflective thinking skills.